PENGARUH PENGUKURAN DAN MANAJEMEN KINERJA TERHADAP KINERJA BISNIS DAN KINERJA KEBERLANJUTAN DENGAN PERAN MEDIASI TATA KELOLA SISI PENAWARAN PADA UMKM CILEUNGSI - Dewi Kinanti Khasanah; Wahyuningsih Santosa; Dorina Widowati; Anya Sitaresmi Pribadi (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the effect of Performance Measurement and Management on Business Performance and Sustainability Performance, with the mediating role of Supply-Side Governance in medium-sized enterprises in Cileungsi, Indonesia. This research employs a quantitative approach using a cross-sectional design involving 150 respondents from three manufacturing companies selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).The results indicate that Performance Measurement and Management significantly affect Business Performance but do not directly influence Sustainability Performance. Business Performance significantly affects Sustainability Performance, suggesting that financial and operational stability serves as a prerequisite for sustainability investments.This study contributes theoretically by integrating performance measurement, supply chain governance, and the dual outcomes of business and sustainability performance into a comprehensive model within the context of local Indonesian firms. Practically, the findings suggest that companies should prioritize operational and financial stability through structured performance measurement systems before implementing resource-intensive sustainability programs, while policymakers should develop assistance programs that integrate performance measurement with sustainability indicators to enhance competitiveness in the global market.